Bilateral calcaneal stress fractures in two cats. (30th April 2015) - Cantatore, M.; Clements, D. N.
<x xml:space="preserve">Abstract</x> Two cats that developed bilateral calcaneal stress fractures are reported. One cat developed lameness associated with incomplete fractures at the base of both calcanei, both of which progressed to acute, complete fractures 2 months later. The second cat presented with acute complete calcaneal fracture, with evidence of remodelling of the contralateral calcaneus, which subsequently fractured two years later. The calcaneal fractures were successfully stabilised with lateral bone plates in each case. Stress fractures were suspected because of the bilateral nature, the simple and similar configuration, the consistent location of the fractures, the absence of other signs of trauma in both cases and the suspected insidious onset of the lameness. The feline calcaneus is susceptible to stress fracture, and cats presenting with calcaneal fractures without evidence of trauma should be evaluated for concurrent skeletal pathology.